Avenues for the Economic Assessment of Agricultural Lands in the Development of the Agricultural Industry - Shapovalov D.A. (EDP Sciences, 2021)
The authors consider the importance of digital technologies in the agro-industrial complex of Russia. The conclusion about the role of universities in this process has been made. Higher education institutions play a dual role. They train professional personnel having all required competencies and should be in line with all the latest innovative research projects that create a scientific and technical basis for the digital transformation of the national agriculture. The State University of Land Management has conducted research on digital land management, remote sensing tools used for the purposes of the real estate cadastre, land monitoring, and real estate assessment.